Orgasmology - Jagose, Annamarie (Book collections on Project MUSE., 2013)
In this long-awaited work, the queer theorist Annamarie Jagose demonstrates that attention to orgasm as an object of queer and feminist thought reveals much about gender, agency, history, and modernity.